Integration of health education for sustainable development: Sabah's initiatives - Mohd Zaki Ishak; Hamzah Md Omar (Sense Publishers, 2012)
Sabah, located north of Borneo, is bordered by Sarawak on its south-west and by East Kalimantan of Indonesia to the south. The area that Sabah encompasses-73,711 square kilometers-makes the state the second largest in Malaysia. Sabah is popularly known as the land below the wind.